Tantangan Pengembangan Koperasi dalam Era PJP II - Revrisond Baswir (Universitas Islam Indonesia, 1995)
The role of cooperatives in Indonesian economic development is basically as a constructor of people's economic power. As such, during the first Indonesian long term development period, cooperatives had achieve a very significant progress. It's number increased from 9,339 to 39,031 during the period, and the amount of it's member increased significantlyfrom only TJ million to 33.0 million. In addition, while it's working capital rised from Rp. 21.9 billion to Rp. 3.1 trillion, it's sales volume rised from Rp. 74,0 billion to Rp. 3.8 trillion. However, in compare to another business sectors, cooperatives still left far behind. It is total amount of asset accounted only about 0.5% of Indonesian total business asset, and it's sales volume accounted only about 2.3% of Indonesian total business sales volume. Based on the facts, the author then analyze the factors causing that unequal condition and propose the methods to accelerate the progress of cooperatives. In the internal sector, the author suggest cooperatives to put emphasize on the profesionalization of it's institutional management, and on it's human resource development. While in the external sector, in order to promote fair capital distribution and fair business competition, the author suggest the government to increase it's control toward Indonesian banking practise.